Shaping Innovativeness and Creativity with Electronic Human Resource Management (e-HRM) - Samuel Ebie (Knowledge Management: An International Journal, 2015)
The purpose of this paper is to explore the relationship between e-HRM and a firm’s ability to becomeinnovative and creative, and then develop a conceptual framework. The proposed framework aims to add to theunderstanding of the way e-HRM creates competitive advantages and contributes to sustainable business performance.Through the exploration of relevant literature a conceptual model underpinned by a combination of the dynamiccapabilities, organisational learning and knowledge management theories is proposed. This paper proposes an answer tohow e-HRM can influence business performance. The authors suggest that e-HRM can be linked to organisationalinnovativeness and creativity through its potential to influence employee innovativeness and employee creativity, whichmay in turn lead to superior business performance. The paper may help the HR function to better understand anotherway e-HRM can be used to contribute to sustainable business performance. This paper contributes to the existingknowledge by shedding some light on the processes through which e-HRM can influence sustainable businessperformance. The proposed framework is an original complete model that could support future research.